Estudio sobre la satisfacción de los usuarios de una biblioteca hospitalaria - Escudero-gómez, Cristina; Solís-muñoz, Montserrat; Alonso-durán, Margarita (Revista General de Información y Documentación, 2008)
To know the opinion of the users of the Hospital Puerta de Hierro Library with regard to services offered. Development: Observational, cross-sectional study performed in 2002, with a 28 questions questionnaire: 5 closed queries, 3 open queries and 20 general questions, following Likert scale with a scoring from 1 (very poor) to 6 (very satisfactory). 106 questionnaires were collected. Professionalism and staff good manners are the more valued by the library users. The worst are the dimensions of the reading room scarce collection of journals and books on specialities and furniture. Physicians and other medical staff are the less satisfied professionals Conclusions: Library users have expressed a medium-high degree of satisfaction in regard to facilities while they expressed a low degree of satisfaction in regard to infrastructure, furniture and dimensions of the reading room. [ESCUDERO GÓMEZ, C. 2007. [Satisfaction of users in a University Hospital Library]. Revista General de información y documentación